2023
DOI: 10.7150/thno.84650
|View full text |Cite
|
Sign up to set email alerts
|

Outer membrane vesicles derived from gut microbiota mediate tubulointerstitial inflammation: a potential new mechanism for diabetic kidney disease

Abstract: Rationale: Chronic tubulointerstitial inflammation is a common pathological process in diabetic kidney disease (DKD). However, its underlying mechanism is largely unknown. This study aims at investigating the role of gut microbiota-derived outer membrane vesicles (OMVs) in tubulointerstitial inflammation in DKD. Methods: Gut microbiota in diabetes mellitus rats was manipulated by microbiota depletion and fecal microbiota transplantation to explore its role in tubulointerstitial inflammation. To check the direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 53 publications
0
3
0
Order By: Relevance
“…A significantly higher concentration of BEVs was observed in patients with T2DM than in the healthy population among stool, serum, and urine ( Nah et al, 2019 ). In diabetes animal model, intestinal microbiota-derived OMVs are also increased ( Chen et al, 2023 ). Furthermore, gut microbe-derived EVs were reported to permeate the intestinal barrier and enter the bloodstream followed by distribution to distant metabolic organs (e.g., adipose tissue, liver, and skeletal muscle), where they trigger insulin resistance and damage glucose metabolism ( Choi et al, 2015 ; Nah et al, 2019 ; Bittel et al, 2021 ).…”
Section: Physiological and Pathological Roles Of Bevs In Specific Sys...mentioning
confidence: 99%
“…A significantly higher concentration of BEVs was observed in patients with T2DM than in the healthy population among stool, serum, and urine ( Nah et al, 2019 ). In diabetes animal model, intestinal microbiota-derived OMVs are also increased ( Chen et al, 2023 ). Furthermore, gut microbe-derived EVs were reported to permeate the intestinal barrier and enter the bloodstream followed by distribution to distant metabolic organs (e.g., adipose tissue, liver, and skeletal muscle), where they trigger insulin resistance and damage glucose metabolism ( Choi et al, 2015 ; Nah et al, 2019 ; Bittel et al, 2021 ).…”
Section: Physiological and Pathological Roles Of Bevs In Specific Sys...mentioning
confidence: 99%
“…DN patients exhibited dysbiosis in the gut microbiota, manifested by increased levels of Lactobacillus , Megaphaera and Sutterella , as well as decreased levels of Lachnochlostridium and Roseburia ( Du et al, 2021 ). Recent research has demonstrated that gut microbiota-derived outer membrane vesicles can promote DN progression by activating tubulointerstitial inflammation ( Chen et al, 2023 ). Notably, the diversity of the gut viruses was significantly reduced in DN patients ( Fan et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, increasing attention has been focused on the role of the gut microbiota in human health, with growing evidence suggesting its involvement in the pathogenesis of DKD ( 12 , 13 ). Dysbiotic gut microbiota in DKD patients often exhibits an increase in pathogenic bacteria and a decrease in beneficial bacteria, resulting in an abnormal colony structure dominated by Gram-negative facultative anaerobic bacteria ( 14 ).…”
Section: Introductionmentioning
confidence: 99%